2018
DOI: 10.1002/oa.2698
|View full text |Cite
|
Sign up to set email alerts
|

Exploring ideas about isotopic variation in breastfeeding and weaning within and between populations: Case studies from the American midcontinent

Abstract: Infant feeding practices are partially constrained by the biological demands of infants and mothers but vary within those constraints based on factors such as subsistence practices, health, class and ethnic variations, and the presence or absence of foods that can be substituted for breastmilk. Over the past 20 years, nitrogen stable isotope ratios have been used to explore infant feeding practices in past populations. Recent studies have moved from normative approaches primarily focused on weaning time to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In many cases, discrete archaeological cemetery populations limit the potential for cross-status analysis, with burial populations explicitly recognized as elite (e.g., Gregoire, 2019) or poor (e.g., Väre et al, 2022). In other studies, differences in status may be present, but are strongly correlated with other variables under analysis, including mobility, changing subsistence practices, demography, or cultural chronology (e.g., Pfeiffer et al, 2017;Scharlotta et al, 2018;Schurr, 2018). Because of uncertainty regarding the inheritance of status, markers of individual burial status do not necessarily imply that parents enjoyed the same status.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, discrete archaeological cemetery populations limit the potential for cross-status analysis, with burial populations explicitly recognized as elite (e.g., Gregoire, 2019) or poor (e.g., Väre et al, 2022). In other studies, differences in status may be present, but are strongly correlated with other variables under analysis, including mobility, changing subsistence practices, demography, or cultural chronology (e.g., Pfeiffer et al, 2017;Scharlotta et al, 2018;Schurr, 2018). Because of uncertainty regarding the inheritance of status, markers of individual burial status do not necessarily imply that parents enjoyed the same status.…”
Section: Discussionmentioning
confidence: 99%
“…There has been growing evidence that other than diet, high levels of stress exposure and malnutrition may also cause variability in the isotopic compositions of humans [29,[78][79][80], mainly in δ 15 N values [79]. However, at Ganj Dareh, the corresponding patterns in both δ 13 C and δ 15 N values of the subadults suggested that diet was a stronger factor than metabolic disruption for the trend in these individuals' isotopic compositions.…”
Section: Stable Carbon and Nitrogen Isotope Analysismentioning
confidence: 99%
“…Refining models to reconstruct breastfeeding and weaning practices (BWPs) of past populations is of great interest to bioanthropologists, as it provides information about demographic patterns, health [ 1 5 ], non-adult rearing practices [ 6 , 7 ], and subsistence strategies [ 8 10 ]. In relation to paleodemography, higher fertility rates and reduced births intervals have been associated with shorter breastfeeding stages [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%